A new voice from Sardinia: Uromenus annae (Targioni-Tozzetti, 1881 (Insecta: Orthoptera: Tettigoniidae: Bradyporinae: Ephippigerini) - Buzzetti, Filippo Maria; Brizio, Cesare; Fontana, Paolo; Massa, Bruno (Zootaxa, 2019)
Recent findings of the Sardinian endemic Bushcricket Uromenus annae (Targioni Tozzetti, 1881) allowed the authors to retrace the nomenclatorial history of the species. The rearing of living specimens resulted in the recording of the male song, previously unknown. Since the Neotype previously established by Fontana & Buzzetti (2001) is lost, a new Neotype is here designated. Affinities with other congeneric species are discussed.